Energijska bilanca občine Tolmin - Drole, Miran (Strojniški vestnik, 2002)
The energy balance of the Tolmin municipality Tolmin is presented in this paper. All types of energy coming from renewable and nonrenewable sources, which are within or crossing the borders of the municipality, are precisely analyzed. The energy supply is studied in terms of the type of energy source and consumer. A comparison is made with the data that applies to the whole Slovenia.
Keywords: bilance energijske; vrste energije; oskrba z energijo; poraba energije; energetika; energijska bilanca; Tolmin